Hubungan Sistem Akuntansi Keuangan Daerah Dengan Kualitas Laporan Keuangan Pada Badan Pengelolaan Keuangan & Aset Daerah Kota Bandar Lampung - Syamsu Rizal; Tri Suari (Universitas Bandar Lampung (UBL), 2014)
The research conducted there is not aimed at the relationship between financial accounting system area with quality accountability on the administration of the city of Bandar Lampung. The Data used in this research was the qualitative data in the form of a questionnaire which is processed into quantitative data with the forms of tabulate data. Test data was conducted to test the validity, reliability, and normality. Test your hypothesis by using correlation method of product moment. Results of this study stated that the financial accounting system of regional relations in the agency financial management Asset & Bandar Lampung city areas were in accordance with the established guidelines. All cycle stages have been run well. So too with the completeness of his or her financial report items were in accordance with the provisions of the financial statements comprising a SKPD Report realization of budget, balance sheet, and notes to the financial statements. Record-keeping and transaction classification comes from ledger, evidence which was recorded in a book journal. For those transactions are the same, recorded in the book of specialized journals. Transactions have been recorded and classified in a journal, each month or other period will be summarized and published in a book of accounts. Accounting Data that have been recorded in the ledgers of accounts presented in the form of financial statements that report the realization of the budget, the balance sheet and notes to the financial statements.